Acceleration clause in financing agreements - García Long, Sergio (2022)
This paper explains the contractual structure of the acceleration clause, or early maturity of the contract term. This clause is typical of financing agreements and is the principal contractual remedy to recover the capital and the total expected profit of the contract.Although the law allows this remedy for certain situations, contractual practice has proposed a more complex scheme that better accommodates the risks involved in a financing. The study of the acceleration clause makes it possible to overcome the divorce observed between the legal remedies of the Civil Code and the conventional remedies of financial contractual practice.